Manufacturing and Characterization of a Deformable Membrane with Integrated Temperature Sensors and Heating Structures in Low Temperature Co‐fired Ceramics. Issue 3 (10th April 2013) - Gutzeit, Nam; Müller, Jens; Reinlein, Claudia; Gebhardt, Sylvia
<x xml:space="preserve">Abstract</x> In this article, the challenging manufacturing process of a deformable mirror for the wave front correction of a high energy laser is described. During this process, the low temperature co‐fired ceramic (LTCC) membrane as the base component with integrated sensors must endure several postfire processes at temperatures of up to 900°C without any degradation of the sensors' characteristics. To optimize the sensors, various combinations of resistor and conductor pastes and different geometries are characterized. The usability and the performance of the sensor elements after temperature treatment are investigated by measuring the resistance and its resistance temperature characteristic.